Comparison of knowledge, attitude and practice on stroke knowledge in Malaysia and other nations: A review of literature - Sowtali, Siti Noorkhairina; Mohd Yusoff, Dariah; Harith, Sakinah; Mohamed, Monniaty (International Medical Journal, 2017)
Background: There is an increasing trend of stroke occurrence among Malaysian populations recently. Thus, there is a need for further early management and secondary prevention of stroke. Objectives: To provide an overview on knowledge, attitude and practice (KAP) had been carried out among stroke patients and general population. Data sources: Published survey studies on KAP had been carried out among stroke patients general population in Malaysia and globally. Review methods: Searches were conducted in two data-bases (ProQuest, EBSCOhost). Reviews were included, if these were based on a survey study that measures KAP between 2005 and 2015. The authors had focused the survey study design, population and sampling method highlighting the tools and interview strategy used in order to obtain the information on KAP. The scope of interest were perceptions towards stroke, knowledge on risk factors, signs and symptoms of stroke and its association with socio-demography background of the participants. Results: A total of 22 articles were reviewed included, but none of them from Malaysia studies. However, only 14 were reviewed systematically on the basis of its completeness for quantitative synthesis. In this article, we had reviewed the existing literatures on the scope mentioned earlier and compared it with those of developed countries. Findings highlighted the level of stroke knowledge on risk factors as well as signs and symptoms were range from moderate to poor. This knowledge level was found to be associated with age, gender, education level and income status. Conclusion: Study on KAP is crucial in order to increase the awareness about stroke disease on the risk factors management, administration of appropriate treatment as well as further secondary prevention. This findings may be adopted in Malaysia to improve awareness and knowledge specifically for the stroke patients and their family members and among the public generally.